1996
DOI: 10.1159/000237379
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of Docosahexaenoic and Eicosapentaenoic Acids in Phorbol-Ester-lnduced Mouse Ear Inflammation

Abstract: Laboratory animal models and clinical studies suggest that dietary n-3 fatty acids are beneficial in diseases with an inflammatory component such as rheumatoid arthritis or psoriasis. In the present study we investigated the effect of purified docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on phorbol ester (TPA)-induced acute inflammation. Mice were fed for 6 weeks a diet containing 5% corn oil enriched with either 1% DHA or 1% EPA and compared with a group receiving 6% corn oil only. The dietary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…DHA is highly enriched in the neuronal or synaptic membrane (Salem, 1989), and its depletion can lead to increased n-6/ n-3 ratios, resulting in inflammation (De Caterina et al, 1994;Raederstorff et al, 1996;Simopoulos, 2002) or excessive oxidative stress (Komatsu et al, 2003), two conditions that enhance A␤ production (Sastre et al, 2003) and are present in AD and transgenic mice (Akiyama et al, 2000;Lim et al, 2000;Pratico et al, 2001;Grundman et al, 2002). Inflammatory cytokines and oxidative stress induce BACE expression and activity (Tamagno et al, 2002;Sastre et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHA is highly enriched in the neuronal or synaptic membrane (Salem, 1989), and its depletion can lead to increased n-6/ n-3 ratios, resulting in inflammation (De Caterina et al, 1994;Raederstorff et al, 1996;Simopoulos, 2002) or excessive oxidative stress (Komatsu et al, 2003), two conditions that enhance A␤ production (Sastre et al, 2003) and are present in AD and transgenic mice (Akiyama et al, 2000;Lim et al, 2000;Pratico et al, 2001;Grundman et al, 2002). Inflammatory cytokines and oxidative stress induce BACE expression and activity (Tamagno et al, 2002;Sastre et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, whereas ␣-secretase expression appears more or less constitutive (Sisodia, 1992;Lammich et al, 1999;Lopez-Perez et al, 2001), BACE1 expression in neuronal cells has been reported to be increased by both proinflammatory cytokines (Sastre et al, 2003) and oxidative damage (Tamagno et al, 2002). n-3 PUFAs have been reported to be antiinflammatory (De Caterina et al, 1994;Raederstorff et al, 1996;Simopoulos, 2002) and to reduce oxidative damage (Komatsu et al, 2003), consistent with protein carbonyl reduction with high-DHA diets (Calon et al, 2004). Therefore, BACE1 mRNA levels in animals on low-and high-DHA diets were analyzed by real- …”
Section: Bace Expression Was Unchanged By Dietary Pufamentioning
confidence: 95%
“…Topical application of PMA triggers prominent neutrophil migration and macrophage activation in the skin. TNF-a, IL-6, and IL-1b, along with proinflammatory lipids such as prostaglandin E2 and leukotriene B4, are induced by topical PMA (Raederstorff et al, 1996;Jang and Pezzuto 1998;Dong et al, 2013). We examined the effect of compd3 on the mRNA levels of IL-23, IL-17F, IL-13, and IL-22 in this model.…”
Section: Resultsmentioning
confidence: 99%
“…Fish oil and n-3 PUFA are used in the treatment of inflammatory disorders, either in experimental models (17)(18)(19)(20) or clinically (6,7,(21)(22)(23). They reduce the synthesis of pro-inflammatory arachidonic acid-derived eicosanoids (8,9), tumor necrosis factor, and interleukin-1 production (24,25), and superoxide anion release by polymorphonuclear cells (10) in vitro.…”
Section: Discussionmentioning
confidence: 99%